Literasi Pegawai Bapenda pada Wajib Pajak di Kabupaten Gowa - Sakia Putri Samsul; Andi Kartika Kusnasriyanti; Muryani Arsal (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines how regulatory, communicative, and digital literacy among employees of the Gowa Regional Revenue Agency influences tax service quality and taxpayer compliance. A phenomenological qualitative approach was applied through interviews, observations, and document reviews involving employees and taxpayers. The findings indicate that uneven regulatory literacy, varying communication skills, and limited digital literacy contribute to inconsistent services. The study highlights the need to strengthen employee competencies as an implication for improving regional tax service quality.